2022
DOI: 10.1002/jmr.2987
|View full text |Cite
|
Sign up to set email alerts
|

Screening of in vitro and in silico effect of Fluorophenylthiourea compounds on glucose 6‐phosphate dehydrogenase and 6‐phosphogluconate dehydrogenase enzymes

Abstract: Inhibition studies of enzymes in the pentose phosphate pathway (PPP) have recently emerged as a promising technique for pharmacological intervention in several illnesses. Glucose 6-phosphate dehydrogenase (G6PD) and 6-phosphogluconate dehydrogenase (6PGD) are the most important enzymes of the PPP. For this purpose, in the current study, we examined the effect of some fluorophenylthiourea on G6PD and 6PGD enzyme activity. These compounds exhibited moderate inhibitory activity against G6PD and 6PGD with K I valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 106 publications
0
1
0
Order By: Relevance
“…Protein and enzyme activities were then measured. Eluates showing activity were stored at 4 °C for further study [20–21] …”
Section: Methodsmentioning
confidence: 99%
“…Protein and enzyme activities were then measured. Eluates showing activity were stored at 4 °C for further study [20–21] …”
Section: Methodsmentioning
confidence: 99%
“…06 μM. In a study conducted by Yıldız et al65 the impact of several fluorophenylthiourea compounds on the 6PGD enzyme was investigated. Their findings revealed that among these compounds, 2-fluorophenylthiourea exhibited the most pronounced inhibitory effect on this enzyme.…”
mentioning
confidence: 99%